Implementation of Community Empowerment to Overcome Poverty through the Mandiri National Community Empowerment Program (PNPM) Viewed from an Islamic Economic Perspective - Alfi Andriansyah Harahap; Mustapa Khamal Rokan; Muhammad Ikhsan Harahap (Yayasan Riset dan Pengembangan Intelektual, 2023)
This research aims to analyze the implementation of the PNPM Mandiri program, find out the obstacles that hinder the implementation of the program, as well as find out and evaluate policy criteria, efforts to implement policy programs to improve community welfare in Padang Garugur Village. This research uses a descriptive research method with a qualitative approach, technical data collection carried out through interviews, observation and documentation. Based on the results of discussions on the Mandiri National Community Empowerment Program (PNPM) in Padang Garugur Village, it is a policy in the welfare improvement program in Padang Garugur Village. In general, the National Community Empowerment Program is implemented in 4 (four) stages, including: Activity Planning, Activity Implementation, Control, Supervision and Evaluation, Conservation. The successful implementation of independent rural PNPM, according to George C. Edwards III,. is greatly influenced by communication factors, implementing resources, the disposition or attitude of the implementers, as well as the bureaucratic structure with activity implementation standards based on existing PTO for activities.